Production Technologies of Various Types of Environmentally Friendly Plasticizer Oils - Antonov, S. A.; Tonkonogov, B. P.; Kilyakova, A. Yu; Dorogochinskaya, V. A. (Chemistry and technology of fuels and oils, 2020)
The production technologies of environmentally friendly plasticizer oils such as TDAE, TRAE, MES, and NAP for the rubber and tire industries are considered. Their basic physicochemical properties and specific application examples are presented. The influence of the types of plasticizer oils on the performance properties of rubber products and tires is described.